NUP98::NSD1 and FLT3/ITD co-expression is an independent predictor of poor prognosis in pediatric AML patients - Jing-wen Wang; Yu-Li; Xing-Ge Yang; Lu-Hong Xu (BMC, 2024)
Abstract Objective Patients who carry NUP98::NSD1 or FLT3/ITD mutations are reported to have poor prognosis. Previous studies have confidently reported that the poor outcome in younger AML patients is owning to dual NUP98::NSD1 and FLT3/ITD positivity, with a high overlap for those two genetic lesions. In this study, we assessed the prognostic value of the presence of both NUP98::NSD1 and FLT3/ITD in pediatric AML patients. Methods We screened a large cohort of 885 pediatric cases from the COG-National Cancer Institute (NCI) TARGET AML cohort and found 57 AML patients with NUP98 rearrangements. Results The frequency of NUP98 gene fusion was 10.8% in 529 patients. NUP98::NSD1 fusion was the most common NUP98 rearrangement, with a frequency of 59.6%(34 of 57). NUP98::NSD1 -positive patients who carried FLT3/ITD mutations had a decreased CR1 or CR2 rate than those patients carried FLT3/ITD mutation alone (P = 0.0001). Moreover, patients harboring both NUP98::NSD1 fusion and FLT3/ITD mutation exhibited inferior event-free survival (EFS, P < 0.001) and overall survival (OS, P = 0.004) than patients who were dual negative for these two genetic lesions. The presence of only NUP98::NSD1 fusion had no significant impact on EFS or OS. We also found that cases with high FLT3/ITD AR levels ( > = 0.5) with or without NUP98::NSD1 had inferior prognosis. Multivariate analysis demonstrated that the presence of both NUP98::NSD1 and FLT3/ITD was an independent prognostic factors for EFS (hazard ratio: 3.2, P = 0.001) in patients with pediatric AML. However, there was no obvious correlation with OS (hazard ratio: 1.3, P = 0.618). Stem cell transplantation did not improve the survival rate of cases with NUP98 fusion or NUP98::NSD1 AML in terms of EFS or OS. Conclusion Presence of both NUP98::NSD1 and FLT3/ITD was found to be an independent factor for dismal prognosis in pediatric AML patients. Notably, lack of FLT3/ITD mutations in NUP98::NSD1 -positive patients did not retain its prognostic value.